Efforts to Preserve Public Interest in Traditional Culinary Products in Order to Improve The Community's Economy - Askarno, Askarno (Green Publisher Indonesia, 2020)
Efforts to preserve traditional culinary are one form of protecting traditional culinary delights from the variety of western foods that enter Indonesia, especially in the Cirebon region. The goal is to preserve food that is rarely traded, even less demanded, therefore researchers want to design a right agarma scheme that still exists in the current era of modernization. This research method with quantitative methods with the number of respondents classified into 2 categories, namely adolescents 12-21 and adults 22-35 years so a total of 30 respondents. The results of this study are adolescent categories, taste, appearance and presentation are important in choosing a food. Meanwhile, the adult category chooses taste, appearance, price, distribution, image and presentation. Traditional culinary interest is an identity of a region and has a cultural entity, that is, 56% of respondents in the youth category choose food because there are cultural values and beliefs in it, and 83% of respondents in the adult category say the same thing. Overall 67% of respondents or the majority of respondents chose food because of cultural values, beliefs. Constraints and the development of traditional food have been evaluated with the advice of researchers, one of which is promoting traditional food with online media, then changing the packaging as attractive as possible with a trademark as a characteristic, easy to remember. In conclusion, the dual traditional culinary mesri and cemplung can still be preserved and developed with more interesting pamasaran methods